2019
DOI: 10.1075/lia.17023.agr
|View full text |Cite
|
Sign up to set email alerts
|

The production of preverbal liaison in Swedish learners of L2 French

Abstract: The acquisition of preverbal liaison (e.g. ils arrivent /ilzaʀiv/) in second language (L2) French has rarely been explored in detail in previous studies on obligatory liaison. In this study, we conducted an elicited imitation test in order to study the influence of proficiency level, modality (spoken or written), and verb frequency on the use of preverbal liaison among 42 Swedish learners of L2 French and 21 native speakers of French. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…However, to elucidate more precisely the individual learning development regarding the plural of grammatical categories, a longitudinal study is needed. Ågren (2008)’s study on the development of plural markers in French as a foreign language showed, however, that learners have more difficulties with correctly spelling adjectives than other word categories independently of their position. The analysis of the test scores in the present study, however, indicates that children’s performance with prenominal adjectives was significantly higher than with postnominal adjectives, a result that is in line with L1 pupils.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, to elucidate more precisely the individual learning development regarding the plural of grammatical categories, a longitudinal study is needed. Ågren (2008)’s study on the development of plural markers in French as a foreign language showed, however, that learners have more difficulties with correctly spelling adjectives than other word categories independently of their position. The analysis of the test scores in the present study, however, indicates that children’s performance with prenominal adjectives was significantly higher than with postnominal adjectives, a result that is in line with L1 pupils.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, adjectives were never marked with plural in the initial stage, and even the most advanced learners did not fully master the agreement on (pre- or postnominal) adjectives. As for the position of the adjectives, it was found to have a clear impact on the spelling development of French as L1 (Fayol et al, 2006) but not on French as L2 (Ågren, 2008). Ågren (2008) could not report clear pluralizing tendencies related to the position of the adjectives.…”
Section: Factors That Influence the Assignment Of Plural And Spellingmentioning
confidence: 98%
See 3 more Smart Citations